Ancient haplotypes of the HLA Class II region - Raymond, Christopher K.; Kas, Arnold; Paddock, Marcia; Qiu, Ruolan; Zhou, Yang; Subramanian, Sandhya; Chang, Jean; Palmieri, Anthony; Haugen, Eric; Kaul, Rajinder; Olson, Maynard V.

(untitled) (Genome Research, 2005)
Allelic variation in codons that specify amino acids that line the peptide-binding pockets of HLA's Class II antigen-presenting proteins is superimposed on strikingly few deeply diverged haplotypes. These haplotypes appear to have been evolving almost independently for tens of millions of years. By complete resequencing of 20 haplotypes across the ∼100-kbp region that spans the HLA-DQA1, -DQB1, and -DRB1 genes, we provide a detailed view of the way in which the genome structure at this locus has been shaped by the interplay of selection, gene-gene interaction, and recombination.